1997
DOI: 10.1063/1.364146
|View full text |Cite
|
Sign up to set email alerts
|

A model of quantum confined state modified by surface potential in porous silicon

Abstract: By analyzing various experimental photoluminescence (PL) and photoluminescence excitation (PLE) spectra in porous silicon (PS), we have found that the PL spectra in PS are characterized by the transitions among the quantum confined states in nanoscale Si which are influenced by the surface chemical bonds. Since the size of silicon filament is comparable to that of surface potential, its electron states are modified by the surface potential. We use a two-dimensional state-dependent surface potential to model th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…2,3 The origin of light emission has been extensively studied. [4][5][6] The similarity between PL and EL spectra indicates that a common recombination mechanism is involved in both cases but the quantum efficiency of the EL is smaller than that of the PL by at least one order of magnitude. In order to improve the efficiency, it is important to study the influence of recombination centers, surface states, and electrical contacts on the EL and PL.…”
Section: Introductionmentioning
confidence: 97%
“…2,3 The origin of light emission has been extensively studied. [4][5][6] The similarity between PL and EL spectra indicates that a common recombination mechanism is involved in both cases but the quantum efficiency of the EL is smaller than that of the PL by at least one order of magnitude. In order to improve the efficiency, it is important to study the influence of recombination centers, surface states, and electrical contacts on the EL and PL.…”
Section: Introductionmentioning
confidence: 97%
“…With increasing the storage time, the Fe 2 O 3 layer will thicken as a result of the increase of the Fe-O bond density. 15 If considering the presence of a transition region between the ␤-FeSi 2 and Fe 2 O 3 layers and its thinning caused by its stor-age in air, we found that the band-mixing model, 14 which can give the energy levels of electrons and holes confined in the Si/ FeSi 2 nanocomposite consisting of nanocrystalline Si core, interfacial FeSi 2 layer, and outer Fe 2 O 3 crust, can explain very well the observed PL intensity increase with the sample storage time and the pinning behavior of the PL peak position. This implies that the PL behavior from the FePS samples is related to both the quantum confinement of Si nanocrystal and its surface passivation ͑the formation of Fe-Si and Fe-O bonds͒.…”
Section: Resultsmentioning
confidence: 89%
“…For PS, many experiments have demonstrated that its luminescence property is not only determined by the quantum confinement effect of Si nanocrystals but also controlled by the surface chemical bonds. [8][9][10][11][12][13][14] Both the surface layer and nc-Si core constitute a nanoparticle composite. Naturally, its luminescence is a result of the interaction of the two nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…To get a comprehensive understanding of underlying physical phenomena, the porous Si has been intensively studied using various theoretical methods, namely by model calculations [18,19], effective mass approximation [20], tight binding [21,22], density functional theory [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%